Tiktok Social Media as a Means of Small and Medium Business Promotion - Hasim, Hasim; Sherlina, Lina (Riviera Publishing, 2022)
The clothing industry is a business that has a very fast development. Now the clothing industry has begun to be divided specifically, one of which is the clothing industry plus size. The current Covid-19 pandemic has an impact on micro, small and medium enterprises so that many businesses suffer losses. There are restrictions on community activities during the pandemic, digital platforms can be an alternative so that they can continue to carry out business activities. Efforts to increase the income of micro, small and medium enterprises need to promote online, one of which is using Tiktok social media. The focus of this research is on the promotion strategy of micro, small and medium plus size clothing businesses to increase sales during the Covid-19 pandemic by utilizing Tiktok social media. The purpose of this study was to find out the promotional strategies through Tiktok social media used by plus size clothing businessmen during the pandemic, what support platforms were used to maximize promotional results, the differences in promotional strategies and the obstacles experienced before and during the Covid-19 pandemic. 19. This study uses a qualitative constructivism method with data collection techniques through in-depth interviews, observations, and document studies. The results of this study suggest that micro, small, and medium-sized plus size clothing businesses can survive and increase their sales during the Covid-19 pandemic by providing a variety of contemporary clothing that is needed by consumers. Using Tiktok for promotions such as creating content and endorsing the right influencers. Using the Instagram support platform as a place for online product catalogs, Shopee to buy products, and Whatsapp as customer service. Promotions and endorsements on the Tiktok application are effective for increasing sales of plussize clothing during the Covid-16 pandemic.